2014
DOI: 10.5114/pjp.2014.48195
|View full text |Cite
|
Sign up to set email alerts
|

Huge alveolar soft part sarcoma of the retroperitoneum –

Abstract: Alveolar soft part sarcoma (ASPS) is a rare type of neoplasm, typically occurring in adolescents and young adults. Because of the rarity of this disease, there is no standard treatment plan. Chemotherapy and radiotherapy are not effective in this type of malignancy. Surgical excision is considered to be the treatment of choice. We report a case of a young woman with a painless mass in her left lower abdomen. Ultrasonography and CT scan revealed a large (21 cm) hard tumor occupying the left retroperitoneal spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Notably, in the recent studies, a use of antiangiogenic agents, such as bevacizumab and tyrosine kinase inhibitors, such as sunitinib, reported as treatment for metastatic ASPS. 58 Stacchiotti et al 7 reported nine patients with progressive metastatic ASPS who received oral administration of sunitinib 37.5 mg/day. The results were partial response in five cases, stable disease in three, and progression in one.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the recent studies, a use of antiangiogenic agents, such as bevacizumab and tyrosine kinase inhibitors, such as sunitinib, reported as treatment for metastatic ASPS. 58 Stacchiotti et al 7 reported nine patients with progressive metastatic ASPS who received oral administration of sunitinib 37.5 mg/day. The results were partial response in five cases, stable disease in three, and progression in one.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic process of sarcomas located in the retroperitoneum is challenging due to its asymptomatic clinical picture, which was observed in other types of neoplasms as well [3]. Gradual growth of leiomyosarcoma will eventually apply pressure to adjacent structures, provoking abdominal pain, which might manifest as several other diseases.…”
mentioning
confidence: 99%